Net macromineral requirements in male and female Saanen goats - Santos Neto, J. M. [UNESP] (2016)
These experiments estimated Ca, P, Mg, K, and Na requirements of intact male, castrated male, and female Saanen goats. Two experiments were performed: one to determine the net macromineral requirements for maintenance (Exp. 1) and another to determine net macromineral requirements for growth (Exp. 2). In Exp. 1, 75 goats (26 intact males, 25 castrated males, and 24 females) with initial BW (iBW) of 15.76 +/- 0.10 kg were used. These animals were divided in 2 groups: baseline animals and pair-fed animals. Twenty-one goats (8 intact males, 7 castrated males, and 6 females) were slaughtered (16.6 +/- 0.96 kg BW) at the beginning of the experiment to be used as the baseline group. The 54 remaining goats (18 intact males, 18 castrated males, and 18 females) were pair fed in 6 blocks of 3 goats per sex. The goats within each block were then randomly allocated to 1 of 3 levels of intake: ad libitum, restricted fed to 75% of the ad libitum intake, and restricted fed to 50% of ad libitum intake. When the animal fed ad libitum reached 31.2 +/- 0.58 kg BW, it and the other goats from the same block were slaughtered. The effects of sex and level of intake were evaluated in a split-plot design, where sex was the main plot observation and level of intake was the subplot. Daily net macromineral requirements for maintenance did not differ among the sexes (P > 0.05), and the average values obtained were 35.4 mg Ca, 24.7 mg P, 2.5 mg Mg, 5.0 mg K, and 3.30 mg Na per kg BW.d(-1). The net requirements for growth in Exp. 2 were obtained using 58 goats (20 intact males, 20 castrated males, and 18 females) with 15.8 +/- 0.11 kg iBW, all fed ad libitum. These animals were assigned in a completely randomized design and allocated in 3 slaughter weight groups: 16.6 +/- 0.96, 23.1 +/- 1.33, and 31.2 +/- 0.58 kg BW. The net Ca, P, and Mg requirements for growth were not different among the sexes (P > 0.05). There was a sex effect on net K and Na requirements for growth (P < 0.05). The net K requirements for growth (g/kg ADG) of intact males were greater (P = 0.03) and increased approximately 16%, whereas females and castrated males decreased approximately 11% as BW increased from 15 to 30 kg BW. The net Na requirements for growth (g/kg ADG) increased 9.5% for intact males and decreased 22% for females when the goats grew from 15 to 30 kg BW. Sex, therefore, affects net K and Na requirements for growth, but it does not affect net macromineral requirements for maintenance in Saanen goats.